Effects of 5-azaC on Iridoid Glycoside Accumulation and DNA Methylation in Rehmannia glutinosa - Dong, Tianyu; Song, Shanglin; Wang, Ying; Yang, Ruixue; Chen, Peilei; Su, Jiuchang; Ding, Xinru; Liu, Yongkang; Duan, Hongying (Frontiers in Plant Science, 2022)
Iridoid glycoside is important the secondary metabolite and the main active components in Rehmannia glutinosa. However, the mechanisms that underlie the regulation of iridoid glycoside biosynthesis remain poorly understood in R. glutinosa. Herein, the analysis of RNA-seq data revealed that 3394 unigenes related with biosynthesis of secondary metabolites were identified in R. glutinosa. 357 unigenes were involved in iridoid glycoside synthesis, in which the highly conservative genes, such as DXS, DXR, GPPS, G10H, and 10HGO, in organisms were overexpressed. The analysis of above genes confirmed that the co-occurrence ratio of DXS, DXR, and GPPS were high in plants. Further, our results showed that under normal and 5-azacytidine (5-azaC) treatment, the expression levels of DXS, DXR, GPPS, G10H, and 10HGO was consistent with the iridoid glycoside accumulation in R. glutinosa, in which the application of the different concentrations of 5-azaC, especially 50 μM 5-azaC, could significantly upregulate the expression of five genes above and iridoid glycoside content. In addition, the changes in the spatiotemporal specificity of degree and levels of DNA methylation were observed in R. glutinosa, in which the hemi-methylation was the main reason for the change of DNA methylation levels. Similar to the changes in 5-methyl cytosine (5mC) content, the DNA demethylation could be induced by 5-azaC and responded in a dose-dependent manner to 15, 50, and 100 μM 5-azaC. Taken together, the expression of iridoid glycoside synthesis gene were upregulated by the demethylation in R. glutinosa, followed by triggering the iridoid glycoside accumulation. These ﬁndings not only identify the key genes of iridoid glycoside synthesis from R. glutinosa, but expand our current knowledge of the function of methylation in iridoid glycoside accumulation.